Molecular Characterization of Multidrug-Resistant Yersinia enterocolitica From Foodborne Outbreaks in Sweden - Karlsson, Philip A.; Tano, Eva; Jernberg, Cecilia; Hickman, Rachel A.; Guy, Lionel; Järhult, Josef D.; Wang, Helen (Frontiers in Microbiology, 2021)
The foodborne pathogen Yersinia enterocolitica causes gastrointestinal infections worldwide. In the spring of 2019, the Swedish Public Health Agency and Statens Serum Institut in Denmark independently identified an outbreak caused by Yersinia enterocolitica 4/O:3 that after sequence comparison turned out to be a cross-border outbreak. A trace-back investigation suggested shipments of fresh prewashed spinach from Italy as a common source for the outbreak. Here, we determined the genome sequences of five Y. enterocolitica clinical isolates during the Swedish outbreak using a combination of Illumina HiSeq short-read and Nanopore Technologies’ MinION long-read whole-genome sequencing. WGS results showed that all clinical strains have a fully assembled chromosome of approximately 4.6 Mbp in size and a 72-kbp virulence plasmid; one of the strains was carrying an additional 5.7-kbp plasmid, pYE-tet. All strains showed a high pathogen probability score (87.5%) with associated genes for virulence, all of which are closely related to an earlier clinical strain Y11 from Germany. In addition, we identified a chromosomally encoded multidrug-resistance cassette carrying resistance genes against chloramphenicol (catA1), streptomycin (aadA1), sulfonamides (sul1), and a mercury resistance module. This chromosomally encoded Tn2670 transposon has previously been reported associated with IncFII plasmids in Enterobacteriaceae: a Shigella flexneri clinical isolate from Japan in 1950s, a Klebsiella pneumoniae outbreak from Australia in 1997, and Salmonella enterica serovar Typhimurium. Interestingly, we identified an additional 5.7-kbp plasmid with tetB (encoding an ABC transporter), Rep, and its own ORI and ORIt sites, sharing high homology with small tetB-Rep plasmids from Pasteurellaceae. This is the first time that Tn2670 and Pasteurellaceae plasmids have been reported in Y. enterocolitica. Taken together, our study showed that the Swedish Y. enterocolitica outbreak strains acquired multi-antibiotic and metal-resistance genes through horizontal gene transfer, suggesting a potential reservoir of intraspecies dissemination of multidrug-resistance genes among foodborne pathogens. This study also highlights the concern of food-chain contamination of prewashed vegetables as a perpetual hazard against public health.